The Role of Entrepreneurial Ecosystems in Fostering Innovation and Start-Up Growth - Nasratullah Khan; Rahmatullah Amiri; Sayed Abdullah (Universitas Kristen Indonesia Toraja, 2024)
Entrepreneurial ecosystems play a critical role in fostering innovation and supporting start-up growth. This study evaluates key ecosystem components, such as access to funding, mentorship, and networks, in driving entrepreneurial success in developed and developing countries.